Insights into the synergistic effect of ammonium and phosphate-containing additives for a thermally stable vanadium redox flow battery electrolyte - Nguyen, Tam Duy (2020)
In the field of large-scale electrochemical energy storage, the vanadium redox flow battery possesses many advantageous features. However, its performance is hampered by the low stability of the positive electrolyte at high temperatures, raising the necessity to use stabilizing agents. Phosphoric acid is commonly used to thermally stabilize the positive vanadium electrolyte, in place of effective hydrohalic acids additives, e.g. HCl, which have the risk of toxic halogen gas formation. However, the effectivity of phosphoric acid is restricted by its self-precipitation with V(V) ions in the sulfuric acid supported vanadium electrolyte to form VOPO4. In this study, we explore the synergistic effect of ammonium and phosphate ions and show that ammonium ions can effectively prevent the formation of VOPO4, hence leading to a significant improvement of the thermal stabilizing effectivity of ammonium phosphates over phosphoric acid. This study provides an insight into the thermal stabilizing effectivity of ammonium- and phosphate-containing additives for the positive vanadium electrolyte, which is useful for the understanding in the design of new additive formula.